PENINGKATAN FLUKS MEMBRAN DENGAN CARA PERENDAMAN DALAM LARUTAN NATRIUM HIPOKHLORIT - Ahmad, Syahril (LIPI Press, 2009)
Experiment to increase membrane flux by dipping of the membranes into solution of natrium hypochlorite (NaOCl) has been done. The purpose of membranes dipping into solution of natrium hypochlorite is to remove residue of additive that was trapped and remained in membrane pore. Membranes observed were flat membrane made from polysulfone material with dimethylacetamide as a solvent and polyvinyl pyrrolidon (PVP) (MW 10 kDa) as an additive. Membranes were dipped into solution of NaOCl at different concentration they were 3000, 4000, and 5000 ppm with soaking time during 24 hour and as compared membrane was dipped into glycerine 50 %. Flux and rejection of membrane that have been soaked in NaOCl and glycerin 50 % were compared. Results of experiment show that dipping of membrane in NaOCl solution can increase the flux but decrease the coefficient of membrane rejection because of increasing of membrane pore size. The higher the concentrate of NaOCl used for membrane dipping, the greater the flux, but the less the rejection of the membrane.